Ethnic differences in the cost-effectiveness of targeted and mass screening for high cardiovascular risk in the UK: cross-sectional study. Issue 23 (3rd October 2013) - Baker, Jessica; Mitchell, Richard; Lawson, Kenny; Pell, Jill
Abstract : Objectives: To investigate ethnic differences in the cost-effectiveness of targeted and mass screening for high cardiovascular risk. Design: Simulation of two screening strategies (targeted screening of most deprived areas and mass screening) using cross-sectional data from Health Survey for England. Setting: England. Subjects: 9407 adults aged 40–74 years (493 Black Caribbean, 532 Indian, 516 Pakistani/Bangladeshi, 617 Irish and 7249 general population of whom 6633 were White). Main outcome measures: Coverage of high-risk population, number needed to screen to identify one person at high cardiovascular risk and cost-effectiveness of targeted screening, with incremental analysis of expanding targeted to mass screening. Results: Coverage, number needed to screen and cost-effectiveness of targeted screening were better in all ethnic minority groups compared with the White group and general population. Targeted screening would identify 19.2% of high-risk individuals in the general population, and require 4.1 people to be screened to identify one person at high cardiovascular risk at a cost of £98. In the Pakistani/Bangladeshi group, 68.7% of the high-risk population would be identified, and only 2.5 people would need to be screened at a lower cost of £59. In comparison with targeted screening, mass screening was less cost-effective overall but the cost per additional high-risk individual detected was the lowest among the South Asian groups (Indian £130 and Pakistani/Bangladeshi £94). Conclusions: Irrespective of whether cardiovascular screening is targeted or universal, it is more cost-effective in South Asian ethnic groups than in the general population. Therefore, cardiovascular screening has the potential to reduce ethnic health inequalities.